Inequality - Poignant Phenomenon of the Beginning of the 21st Century - Botescu Ion (Ovidius University Annals: Economic Sciences Series, 2018)
Inequality is unfortunately a phenomenon of great relevance for the contemporary period. The increasing differences between the incomes of various social classes have prompted the multiplication of manifestations of individualism, selfishness, etc., thus jeopardizing social stability. The eternal dispute between the liberalism imposed by markets and the need for state intervention to a certain extent in the economy must bring to the fore – together with economic growth – the interests of all the citizens of a country. The accentuation of economic and social inequality over the last decades, the causes that led to this phenomenon and the context where such an evolution of inequality took place represent the main issues addressed in this paper. I wanted to join those who try to draw the attention to the issue of increasing economic and social inequalities among the members of society, in order to raise the awareness of the decisionmaking factors on the chronicization of a phenomenon that could harm everyone on a long-term, including the wealthy citizens of the planet.